Planting the seeds of an environmentally-conscious population through Singapore's city in nature - Nur Aishah Bte Mohamed Z (Nanyang Technological University, 2023)
This paper aims to address the lack of research done on Singapore’s recently introduced “City in Nature” campaign. This campaign represents a significant shift in the country’s approach to greening efforts, from a focus on liveability and economic survival to sustainable development. Using a mixed-method approach consisting of content analysis, discourse analysis and ethnography, this paper seeks to investigate how the state strives to balance development and conservation through “City in Nature”, and how it is perceived by the community. By employing green governmentality and ecological modernisation, we demonstrate the state’s central role in constructing discourse using science and technology to foster environmental stewardship among the community and corporations.